Effect of Quadriceps Set and Manual Traction on Pain in Osteoarthritis - W. Wijianto; Maryam Habibah (P3M Universitas 'Aisyiyah Surakarta, 2023)
Background: Osteoarthritis (OA) is a joint disorder in which progressive loss of articular cartilage occurs and can lead to disability. The most common symptom of osteoarthritis is pain. Usually the pain is exacerbated by use of the joint and relieved by rest. treatment is only aimed at relieving pain, maintaining or increasing mobility, minimizing disability, and improving quality of life. Objective: To determine the effect of quadriceps sets and manual traction on pain in knee osteoarthritis. Methods: This study used a pre-experimental method with a one group pretest and posttest design. Pain measurement was performed using a visual analogue scale (VAS). The data normality analysis test will use Shapiro Wilk while the bivariate analysis uses the paired sample t test, and the multivariate analysis uses a linear regression test. Results: The results obtained from this study, there was a significant effect of manual traction and quadriceps sets on pain p=0.000 (p <0.05) and there was no significant relationship between changes in pain with age (p=0.266) and BMI (p=0.241). Conclusion: There is an effect of giving quadriceps sets and manual traction on the incidence of reducing pain in knee osteoarthritis.